2019
DOI: 10.4314/tjpr.v17i10.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Bufei Yishen</i> formula on klotho gene expression and inflammation-related RIG-I/NF-κB pathway in cigarette smoke extract-treated BEAS-2B cells

Abstract: Purpose: To investigate the anti-inflammatory effect of Bufei yishen formula on chronic obstructive pulmonary disease (COPD) and klotho expression in cigarette smoke extract (CSE)-treated BEAS-2B cells. Methods: Cigarette smoke extract (CSE) was diluted in Dulbecco's modified Eagle's medium (DMEM) and used to treat a COPD cell model established using BEAS-2B cells. The CSE-treated cells were transfected with klotho overexpression plasmid, and the COPD cell model was treated with Bufei yishen formula. Dexametha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a previous study, we found that CSE suppresses the expression of klotho in BEAS-2B cells, whereas BYF can inhibit CSE-induced inflammation by upregulating the expression of klotho. 10 In this study, we found that CSE induced senescence in BEAS-2B cells, whereas BYF could inhibit CSE-induced cellular senescence by upregulating the transcription, expression and secretion of the anti-aging gene klotho. Currently, studies on the mechanism of BYF to alleviate clinical symptoms of COPD patients have focused on the regulation of oxidative stress and immune responses.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a previous study, we found that CSE suppresses the expression of klotho in BEAS-2B cells, whereas BYF can inhibit CSE-induced inflammation by upregulating the expression of klotho. 10 In this study, we found that CSE induced senescence in BEAS-2B cells, whereas BYF could inhibit CSE-induced cellular senescence by upregulating the transcription, expression and secretion of the anti-aging gene klotho. Currently, studies on the mechanism of BYF to alleviate clinical symptoms of COPD patients have focused on the regulation of oxidative stress and immune responses.…”
Section: Discussionmentioning
confidence: 62%
“… 10 Increasing klotho levels in lung epithelial cells reduces CSE-induced inflammation, oxidative stress and cellular senescence. 10 , 11 However, the regulatory mechanisms underlying the downregulation of klotho expression in COPD remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation